(untitled) (Balthazar, 2020)
Biocentrism is the position that considers that morally considerable entities are living beings. However, one of the objections is that if we understand that moral consideration should depend on what is valuable, we would have to conclude that the mere fact of being alive is is not what makes someone morally considerable. Ecocentrism is the position that holds that morally valuable entities are not individuals, but the ecosystems in which they live. In fact, among the positions traditionally defended as ecologists there are serious divergences. Some of them, biocentrists, in particular, can ally themselves with holistic positions such as ecocentrism on certain occasions.